Effect of crystallite orientation and external stress on hydride precipitation and dissolution in Zr2.5%Nb - Vizcaino, Pablo (2014)
Thermal cycling of Zr2.5%Nb pressure tubes specimens containing ∼100 wt ppm H between room temperature and 400 °C produces the dissolution and re-precipitation of zirconium hydride, with a distinctive hysteresis between these two processes. In this work, we have found that the details of the precipitation and dissolution depend on the actual orientation of the α-Zr grains where hydride precipitation takes place. In situ synchrotron X-ray diffraction experiments during such thermal cycles have provided information about hydride precipitation specific to the two most important groups of α-Zr phase orientations, namely crystallites having c-axes parallel (mHoop) and tilted by ∼20° (mTilted) from the tube hoop direction. The results indicate that hydrides precipitate at slightly higher temperatures (∼5 °C), and dissolve at consistently higher temperatures (∼15 °C) in mTilted grains than in mHoop grains. Moreover, application of a tensile stress along the tube hoop direction results in two noticeable effects in hydride precipitation. Firstly, it shifts hydride precipitation towards higher temperatures, at a rate of ∼(0.08 ± 0.02) °C/MPa for hydrides precipitated in the mHoop grains. Secondly, it produces a redistribution of hydrogen between grains of different orientations, increasing hydride precipitation on those α-Zr grains having their c-axes stretched by the external load. A detailed analysis of the diffracted signal shows that such redistribution occurs during the precipitation stage, as a result of changes in the precipitation temperatures for different grain orientations.